Research entitled: "The Impact of Total Quality Management on Human Resources Development" A field study on employees at the Passports and Nationality Authority and Arab and Foreigners Affairs (Albayan Scientific Journal, 2023)
The study aimed to identify the impact of total quality management on the development of human resources for employees in the Passports, Nationality and Arab and Foreign Affairs Department, ElabyarBranch, and the study community consisted of all employees in the study community, which numbered (61) employees. Where a comprehensive survey method was used, the baseline data for the study were collected via a questionnaire. To analyze the data collected from the study community and to achieve the goals of the study, a computer was used and SPSS was used, and this study concluded a set of results, the most important of which are:.1 The results showed that there is a statistically significant effect between continuous improvement and the level of human resource development among members of the study community, as there is an effect between the focus on the customer and the level of human resource development, and there is also a statistically significant effect between support for senior management and the level of human resource development.• While the results generally showed that there is a statistically significant effect between its three dimensions of total quality management and the level of human resource development among the study community members, where the overall determination factor reached R (0.108), which means that approximately 11% of the change in the level of resource development Humanity is due to the change in the dimensions of TQM, and the degree of impact has reached β (0.122), which means that a one-degree increase in the level of TQM dimensions leads to higher levels of human resource development among the study community at a rate of (0.122).3.The results showed that the level of human resources development was somewhat average if compared to the average of the study scale, where the arithmetic average was (2.8136).
Keywords: The quality; Development